A nuclear orthologue of the dNTP triphosphohydrolase SAMHD1 controls dNTP homeostasis and genomic stability in Trypanosoma brucei - Antequera-Parrilla, Pablo; Castillo-Acosta, Víctor M.; Bosch-Navarrete, Cristina; Ruiz-Pérez, Luis Miguel; González-Pacanowska, Dolores (Frontiers in Cellular and Infection Microbiology, 2023)
Maintenance of dNTPs pools in Trypanosoma brucei is dependent on both biosynthetic and degradation pathways that together ensure correct cellular homeostasis throughout the cell cycle which is essential for the preservation of genomic stability. Both the salvage and de novo pathways participate in the provision of pyrimidine dNTPs while purine dNTPs are made available solely through salvage. In order to identify enzymes involved in degradation here we have characterized the role of a trypanosomal SAMHD1 orthologue denominated TbHD82. Our results show that TbHD82 is a nuclear enzyme in both procyclic and bloodstream forms of T. brucei. Knockout forms exhibit a hypermutator phenotype, cell cycle perturbations and an activation of the DNA repair response. Furthermore, dNTP quantification of TbHD82 null mutant cells revealed perturbations in nucleotide metabolism with a substantial accumulation of dATP, dCTP and dTTP. We propose that this HD domain-containing protein present in kinetoplastids plays an essential role acting as a sentinel of genomic fidelity by modulating the unnecessary and detrimental accumulation of dNTPs.